1993
DOI: 10.1007/bf00762591
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the mitochondrial calcium uniporter by antibodies against a 40-kDa glycorproteinT

Abstract: Polyclonal rabbit antibodies against a Ca(2+)-binding mitochondrial glycoprotein were found to inhibit the uniporter-mediated transport of Ca2+ in mitoplasts prepared from rat liver mitochondria. Spermine, a modulator of the uniporter, decreased the inhibition. This glycoprotein of M(r) 40,000, isolated from beef heart mitochondria and earlier shown to form Ca(2+)-conducting channels in black-lipid membranes, thus is a good candidate for being a component of the uniporter. Antibody-IgG was found to specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…In 1979, Bragadin et al, based on indirect data, proposed that the MCU is a gated ion channel [10], and this proposal was eventually directly confirmed in 2004 by Clapham and coworkers by patch clamping of the IMM [58]. A 40-kDa protein apparently capable of catalyzing Ca 2+ uptake in reconstituted liposomes was isolated by Saris and coworkers in 1993 [103]. Whether or not this protein is related to the recently discovered MCU (whose MW is indeed~40 kDa) is not known.…”
Section: The Ca 2+ Toolkit Of Mitochondriamentioning
confidence: 93%
See 1 more Smart Citation
“…In 1979, Bragadin et al, based on indirect data, proposed that the MCU is a gated ion channel [10], and this proposal was eventually directly confirmed in 2004 by Clapham and coworkers by patch clamping of the IMM [58]. A 40-kDa protein apparently capable of catalyzing Ca 2+ uptake in reconstituted liposomes was isolated by Saris and coworkers in 1993 [103]. Whether or not this protein is related to the recently discovered MCU (whose MW is indeed~40 kDa) is not known.…”
Section: The Ca 2+ Toolkit Of Mitochondriamentioning
confidence: 93%
“…Several papers have been published in these three decades [61,83,84,103,106] claiming the identification of either of these proteins, but conclusive unambiguous identification has been obtained only in the last 2 years.…”
Section: The Ca 2+ Toolkit Of Mitochondriamentioning
confidence: 99%
“…At one stage, the best known candidate was the so-called 'P30 glycoprotein', a peripheral glycosylated membrane protein that the authors thought could transport Ca 2 þ across the inner membrane with a mechanism similar to that of classical antibiotic ionophores, such as valinomycin. 19,20 In 1979, based on a series of indirect data, we proposed that the uniporter was a gated ion channel 21 that is an integral protein of the inner mitochondrial membrane. This proposal was never followed up until Clapham and coworkers, by patch clamping the inner mitochondrial membrane, very elegantly showed that the uniporter is indeed a selective divalent cation channel.…”
Section: -18mentioning
confidence: 99%
“…Later, Mironova and coworkers (97) also isolated a 40-kDa Ca 2+ -binding glycoprotein from beef heart mitochondria and found that a 2-kDa peptide fragment in the preparation could reconstitute a ruthenium red-sensitive Ca 2+ selective conductance in black-lipid membranes. Antibodies against this peptide inhibited Ca 2+ uniporter activity in mitoplasts (98). The 2-kDa protein was further purified and formed 20-pS ruthenium red-sensitive channels upon reconstitution (99).…”
Section: The Mitochondrial Ca 2+ Uniportermentioning
confidence: 99%